PENGARUH LAYANAN PERMODALAN DIGITAL TERHADAP KINERJA UMKM - Gainau, Paskanova Christi; Kilay, Trisye Natalia (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2023)
The aim of this research is to examine the influence of digital capital services represented by market aggregator variables on MSME performance. Market aggregator examines the aspect of access to information related to capital for business actors. The research used a survey method through observation and distributing questionnaires to business actors in Ambon City. Samples were taken based on purposive sampling technique. The research results show that digital capital services can significantly boost the performance of MSMEs. Business actors who utilize market aggregator platforms to access capital information encourage them to obtain quality information related to capital decision making so that ultimately it supports business actors to achieve satisfactory business performance. These results also have an impact on the economic sector in general, where when business actors gain access to adequate capital, sales and profit levels can increase. If sales and profits increase then in the long term the business level can increase to the next level. Increasing the level of business certainly encourages an increase in state revenues through taxes, employment, and an increase in gross domestic product (GDP).